UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL BIJI PINANG (Areca catechu L.) TERHADAP Staphylococcus aureus SECARA IN VITRO - ., Jenri Sutrisno (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background: Areca nut potential as antibacterial need scientific studiesas consideration for maximal and directional exploration. Objective: The objective was to confirm the antibacterial activity, to knowthe chemical compounds and to determine Minimum InhibitoryConcentration (MIC) of ethanolic extract of Areca nut. Methods: Ethanolic extract of Areca nut was made from macerationprocess by using ethanol 96%. Antibacterial activity assays was performedusing Kirby-Bauer disc diffusion method against Staphylococcus aureus invitro. Ethanolic extract of Areca nut was diluted in 10 % DMSO to 0,5%;1%; 1,5%; 2%; 2,5%; 3% concentrations. Chloramphenicol and 10%DMSO were also used as control solutions. Result: The result showed that the phytochemical of Areca nut extractcontains phenols, flavonoids, tannin, saponins, triterpenoids, glycosidesand alkaloids. Antibacterial activity was reflected by the diameter of thezone of inhibition around the disc with the average zone of inhibitionobtained from concentrations 2%; 2,5%; 3% in a row was 7,37 mm; 8,56mm; 11,22 mm. Conclusion: Ethanolic extract of Areca nut has antibacterial activiyagainst Staphylococcus aureus in vitro with minimum inhibitoryconcentration (MIC) was 2%.Key words:Â antibacterial, Areca nut ethanolic extract, Staphylococcus aureus 1) Medical School, Faculty of Medicine, Universitas Tanjungpura,Pontianak, West Kalimantan 2) Study Program of Pharmacy, Faculty of Medicine, UniversitasTanjungpura, Pontianak, West Kalimantan 3) Departement of Physiology, Faculty of Medicine, UniversitasTanjungpura , Pontianak, West Kalimantan